Efficacy and sex-specific outcomes after six episodes of percutaneous tibial nerve stimulation treatment on overactive bladder syndrome symptoms - Perez−Martinez, Carlos; Palacios-Galicia, Jose Luis; Vargas-Diaz, Irma B.; Munoz, Alvaro; Cruz, Yolanda (Frontiers in Urology, 2024)
Objective. To investigate the efficacy of six episodes of percutaneous tibial nerve stimulation (PTNS) treatment on overactive bladder (OAB) symptoms in men and women, as well as to determine the duration of the effects over a 6-month period. Methods. Women and men with OAB symptoms participated in the study, which was conducted in accordance with an approved ethical protocol (ISRCTN15733799). Patients underwent six 30-minute PTNS sessions, twice per week. OAB symptoms were assessed using voiding diary, the short form of the Overactive Bladder Symptom Score questionnaire (OAB-q SF), and Patient Perception of Bladder Condition (PPBC), which were self completed by patients before and post-treatment (24 h, and 1, 3 and 6 months). Outcome data were compared for sex and time-points by using two Way ANOVA for Repeated Measures. Results. PTNS treatment significantly improved OAB symptoms and quality of life in men and women. PTNS increased voided volume (p<0.05) and decreased frequency of voiding, nocturia and urgency, at 24 h and up to 6 months (p<0.001). OABq-SF and PPBC scores were significantly decreased after PTNS (p<0.001). Urgency was greater in men than women. The duration of PTNS clinical success on frequency and perception of improvement in quality of life, were greater in women than in men. Conclusions. The clinical effect of six sessions of PTNS strongly suggest the potential for shortening, from the standard 12 sessions, to effectively alleviate OAB symptoms. This therapeutic procedure would reduce both time and economic costs of OAB treatment.